An overview of methods to evaluate uncertainty of deterministic models in decision support. (January 2015) - Uusitalo, Laura; Lehikoinen, Annukka; Helle, Inari; Myrberg, Kai
Abstract: There is an increasing need for environmental management advice that is wide-scoped, covering various interlinked policies, and realistic about the uncertainties related to the possible management actions. To achieve this, efficient decision support integrates the results of pre-existing models. Many environmental models are deterministic, but the uncertainty of their outcomes needs to be estimated when they are utilized for decision support. We review various methods that have been or could be applied to evaluate the uncertainty related to deterministic models' outputs. We cover expert judgement, model emulation, sensitivity analysis, temporal and spatial variability in the model outputs, the use of multiple models, and statistical approaches, and evaluate when these methods are appropriate and what must be taken into account when utilizing them. The best way to evaluate the uncertainty depends on the definitions of the source models and the amount and quality of information available to the modeller. Highlights: We review different types of uncertainty present in environmental modelling. We review methods to evaluate uncertainty related to model results. Best way to evaluate uncertainty depends on the models and available information.